Modified Glasgow Coma Scale and the Alert Verbal Painful Unresponsive Scale for Assessing the Level of Consciousness in Pediatric Critical Care Patients—A Comparative Study - Chaudhary, Richa; Nagula, Karthikeya; Taksande, Amar (Journal of Pediatric Neurology, 2021)
Altered consciousness is a common problem encountered in the pediatric emergency department. Modified Glasgow coma scale (MGCS) has been widely used in pediatric intensive care units (PICUs) for assessing the level of consciousness in children with various illnesses. To compare utility of alert verbal painful unresponsive (AVPU) scale and MGCS for assessing level of consciousness of critically ill patients admitted to PICU. A prospective observational study was conducted at Acharya Vinoba Bhave Rural Hospital in Maharashtra, India on children above the age of 30 days admitted to the PICU from September 2018 to August 2019, fulfilling the inclusion criteria, after obtaining informed consent from the parents. Level of consciousness of the enrolled patients was assessed using the AVPU scale and MGCS. One-way analysis of variance technique was used for data analysis. A total of 74 children were included in the study. A good correlation was observed between the two scales and mean MGCS score of 13.8 (13–15), 11.3 (11–12), 8.09 (7–9), and 3 corresponded to A, V, P, and U, respectively. AVPU scale was comparable to MGCS in assessing level of consciousness in children admitted to PICU. AVPU can be used for initial evaluation of level of consciousness in children presenting with altered consciousness. More detailed MGCS can be used to assess the improvement over time and to decide further treatment strategy.
Keywords: AVPU scale; altered consciousness; children; modified Glasgow coma scale; pediatric intensive care unit